Facing Displacement and a Global Pandemic: Evidence from a Fragile State - Michele Di Maio; Francesco Fasani; Valerio Leone Sciabolazza; Vasco Molini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
We use novel survey data to assess the impact of COVID-19 pandemic on the Libyan population. In our sample, 9.5% of respondents report that a household member has been infected by COVID 19, while 24.7% of them have suffered economic damages and 14.6% have experienced negative health effects due to the pandemic. Our analysis focuses on the differences between IDPs and non-displaced individuals, controlling for individuals and household characteristics, geo-localized measures of economic activity and conflict intensity. Displaced individuals do not experience higher incidence of COVID-19 relative to comparable non-displaced individuals, but are about 60% more likely than non-displaced respondents to report negative economic and health impacts caused by the pandemic. Our results suggest that the larger damages suffered by IDPs can be explained by their weaker economic status - which leads to more food insecurity and indebtedness - and by the discrimination they face in accessing health care.
Keywords: F22; J61; K37; 330; Internally Displaced Persons; COVID-19; Health; Migration; Conflict; Libya